EKSPLORASI MATERIAL INSPIRASI GAYA ART NOUVEAU BERTEMU DENGAN IKON INDONESIA DENGAN METODE ATUMICS - Devanny Gumulya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
History is very essential in design process because to create progress. It requires an understanding of what has already been accomplished. This paper is a learning outcome of history of product design courses in product design of Pelita Harapan University. Art Nouveau is a style that aimed to introduce new art during the 1880s post-industrial revolution in Paris. With its obsession with novelty, Art Nouveau incorporates elements from a variety of cultures, including Japan, Moorish art, nature, and numerous material explorations. Emile Galle, one of the Art Nouveau figures in Paris. He explored and invented numerous new glass techniques such as wheel cutting, acid etching (frosted glass), and glass casing layering. The journal uses of ATUMICS, a method for deriving structured inspiration from artifacts that incorporate technique, utility, material, icon, concept, and shape. The novelty of this journal stems from the combination of two artifacts: the cameo glass technique and an Indonesian icon, the national monument and the rafflesia Arnoldi flower, where the interaction of the two resulted in product design works in fashion accessories. This process demonstrates that the elements that play important role when two artefacts are interacting using the ATUMICS method are technique, relational icon, and concept. Whereas the reciprocal relationship between artifacts on a symbolic level inspires each other in all three dimensions.